Micropropagation of Pittosporum eriocarpum Royle-An Endangered and Endemic Medicinal Tree of North-West Himalaya - Panwar, G. S.; Srivastava, Amber; Srivastava, S. K. (Indian Forester, 2016)
Pittosporum eriocarpum (Pittosporaceae), commonly known as agni, is an endangered and endemic species of North-West Himalaya and facing a grim situation in the wild. Bark of the species is widely used for the preparation of traditional medicines for the treatment of narcotic, expectorant, bronchitis as well. Microprogation of the species has been carried out by using the shoot tip explant and 93.54% shooting was reported in MS medium supplemented with BAP (5.7 Î¼M) and NAA (1.59 Î¼M) with 24.6 average number of shoots and 5.8 cm shoot length. The in vitro regenerated shoots were shifted to the rooting medium and quarter-strength basal MS medium fortified with IBA (7.3Î¼M) was observed as the optimum medium for the root induction and 95.78% rooting was reported with 17.4 average numbers of roots and 3.6 cm root length. After proper development of roots (3 weeks) with average root length 3.6 cm, 50 plantlets were washed properly and shifted to polythene bags containing mixture of vermiculite and soil (1:1w/v) and maintained in the green house. Initially the pots were covered by the transparent polythene bags to ensure the required humidity content and watered with 1/4 modified Hoagland's solution on alternate day. These acclimatized plants were transferred to the field with survival rate of about 84%.